The Relationship Between Protein, Iron, Vitamin C and Vitamin B12 Intake and The Incidence of Anemia - Tamala, Ramtina; Maigoda, Tonny C; Suryani, Desri; Rizal, Ahmad; Okfriani, Yenni (Poltekkes Kemenkes Riau, 2024)
Anemia is a condition when hemoglobin is lower than normal levels. The purpose of this study was to determine the relationship of protein intake, iron, vitamin C and vitamin B12 in adolescent girls of SMKN 3 majoring in culinary. This research method uses analytical observation with a cross sectional method. the sample used in this study was 60 young women majoring in cosmetology taken using simple random sampling. Intake of protein, iron, vitamin C, vitamin B12 using the 3x24 hour Food Recall form and measurement of Hb levels using the Earsy touch GcHb tool. Univariate and bivariate data analysis were processed using the chi-square test with a significance level of a=0.05. Conclusion most of the respondents had insufficient intake of protein, iron and there was a significant relationship, while vitamin c and vitamin B12 with the incidence of anemia did not have a significant relationship.